PENGARUH LAYANAN BIMBINGAN KONSELING, POLA ASUH ORANG TUA, DAN INTERAKSI SOSIAL TERHADAP KEMANDIRIAN PESERTA DIDIK SMP MUHAMMADIYAH 02 SEMARANG - R. Pratiwi R. Pratiwi (BBM (Buletin Bisnis & Manajemen), 2017)
Independence a child in face of life challenge have to earn to be grown early on possibly, in growing independence attitude each, every child need aid in accepting self and also insuffiency dan excess of him. So that environment go to school more than anything else family environment expected to have sensitivity to requirement of child, derestricted possibilities and potency for child self to expand, thereby a child can find way out. Hurlock, E.B (2008). This research have target to know influence of guidance and counseling, pattern of old below and social interaction to student independence in Junior School  Muhammadiyah  02 Semarang. This research is descriptive research with quantitative analysis. Population in this research is stundent and of sampel research counted 65 responden. The technic of collecting data using quisionnaires and the data where tasted and  analyzed using regression analysis with SPSS Ver 17.0 for windows.Based on the result of the data analysis concluded that guidance and counseling, pattern of old below and social interaction have a positive and significan impact to student independence.  Keywords : Guidance and Counseling, Pattern of Old Below, Social Interaction, Student Independence